The Past, Present, and Future of Power Conversion Technologies for Computer, Networking, and Telecom Power Systems - B.M. Rajesh (International Journal of Information Security Engineering, 2023)
The power systems of modern computers, networking, and telecom equipment face formidable challenges due to the ongoing increase in power-density and efficiency requirements. Significant technological breakthroughs in system designs, devices and materials, topology optimization, and packaging/thermal design will be necessary to meet these objectives. To address these challenges, ongoing research and development efforts are being conducted in academia, industry, and government institutions. These efforts aim to revolutionize power system designs, improve energy efficiency, and meet the increasing power demands of contemporary computer, networking, and telecom equipment. This entails developing effective voltage regulators, power converters, and energy storage solutions, while also advancing control algorithms and intelligent power management methods to enhance power consumption optimization and minimize inefficiencies. This study identifies and briefly discusses the main technological issues and emerging trends in each of these important technological fields.
Keywords: Challenges; Power systems; contemporary computer; efficiency demands; growth; networking; power-density; telecom equipment